An observational postmarketing safety registry of patients in the UK, Germany, and Switzerland, who have been prescribed Sativex® (THC:CBD, nabiximols) oromucosal spray - Etges T; Karolia K; Grint T; Taylor A; Lauder H; Daka B; Wright S (Dove Medical Press, 2016)
Tilden Etges, Kari Karolia, Thomas Grint, Adam Taylor, Heather Lauder, Brian Daka, Stephen Wright GW Pharmaceuticals, Cambridge, UK Abstract: The global exposure of Sativex® (Δ9-tetrahydrocannabinol [THC]:cannabidiol [CBD], nabiximols) is estimated to be above 45,000 patient-years since it was given marketing approval for treating treatment-resistant spasticity in multiple sclerosis (MS). An observational registry to collect safety data from patients receiving THC:CBD was set up following its approval in the UK, Germany, and Switzerland, with the aim of determining its long-term safety in clinical practice. Twice a year, the Registry was opened to prescribing physicians to voluntarily report data on patients’ use of THC:CBD, clinically significant adverse events (AEs), and special interest events. The Registry contains data from 941 patients with 2,213.98 patient-years of exposure. Within this cohort, 60% were reported as continuing treatment, while 83% were reported as benefiting from the treatment. Thirty-two percent of patients stopped treatment, with approximately one third citing lack of effectiveness and one quarter citing AEs. Psychiatric AEs of clinical significance were reported in 6% of the patients, 6% reported falls requiring medical attention, and suicidality was reported in 2%. Driving ability was reported to have worsened in 2% of patients, but improved in 7%. AEs were more common during the first month of treatment. The most common treatment-related AEs included dizziness (2.3%) and fatigue (1.7%). There were no signals to indicate abuse, diversion, or dependence. The long-term risk profile from the Registry is consistent with the known (labeled) safety profile of THC:CBD, and therefore supports it being a well-tolerated and beneficial medication for the treatment of MS spasticity. No evidence of new long-term safety concerns has emerged. Keywords: cannabidiol, tetrahydrocannabinol, non-interventional, multiple sclerosis, spasticity, risk management plan